MENGEMBANGKAN STAF ORGANISASI MENJADI SUMBERDAYA MANUSIA STRATEGIK MELALUI BUDAYA MELAYANI PELANGGAN - Sri Suprapti, Ni Wayan (PIRAMIDA; Vol 3, No.1 Juli 2007, 2012)
This paper attempts to apply some marketing and human resource management concepts to high educational area. Higher competition intensity demands a high educational institution to become a learning organization, where its entire member has an ability to learn faster and doing knowledge sharing effectively. In a high educational institution, both of teaching and administration?s staff must develop themselves to become a strategic human resource so they will be able to conduct learning process with high perceived customer value. It will be realized if there is a strong culture for entire member of organization to serve customers, both external and internal.
Keywords: learning organization, perceived customers value, internal and external customers.